ANALISA PENGARUH KINERJA MANDOR TERHADAP KUALITAS PROYEK KONSTRUKSI DI KOTA TUBAN - ., Mushthofa (Universitas 17 Agustus 1945 Surabaya, 2015)
This study analyzed the effect of the performance of supervisors on the quality of construction projects in the city of Tuban. Population of this research is the foreman who led the work force in the execution of a construction project in the city of Tuban. The number of samples in this study were 34 people foreman in construction projects with a value of more than Rp. 250 million and below a value of Rp. 5 Billion. Data collection techniques in this study by taking primary data to find data directly in construction projects and take a secondary data by searching the literature related to this research. Analysis of the data used in this study using multiple linear regression with a comparison of two methods, namely Enter and Stepwise method. Results were analyzed by both methods are equally demonstrate that capability foreman work has a significant influence on the quality of construction projects in the city of Tuban with sig. 0.000 <0.05. Predictive power of the regression model with the Enter method (R-square) which is formed in this test has a value of 94.1%, meaning that the foreman working ability has contributed to the quality of construction projects amounted to 94.1%, while the remaining 5.9% was influenced by variables other than a model. While stepwise (R-square) which is formed in this test has a value of 93.6%, meaning that the foreman working ability has contributed to the quality of construction projects amounted to 93.6%, while the remaining 6.4% is influenced by other variables outside the model.Â The conclusion from this study is that among the factors foreman performance which include: the ability to work foreman, work discipline foreman, the foreman relationship with the project organization and work motivation foreman, the most dominant influence on the quality of construction projects is the capability of working foreman.Keywords: ability, performance, quality